Chapter 37. Training Teachers for Health Workers - Wood, Christopher (My University, 1980)
To develop health services so that they cover a greater proportion of the world 's population we need more health workers, and to train more health workers appropriately we need more teachers. Health workers of all kinds are required and it should be appreciated that there is a continuum of knowledge and skills from the simplest first aider up to the professor of paediatrics. Though there may be disagreement about what individuals or groups should be called - auxiliary, assistant or paramedical - and about the level of knowledge and skills that they should have in general or specialist fields, no health service can function efficiently without staff of all levels. In this chapter al l these people will be called health workers
Book chapter
Keywords: Community Health workers (CHWs); Health service; Primary school; Secondary school; Maternal and child health; Teachers